Taxonomic changes to the Neotropical species of the genus Habroscelimorpha (Coleoptera: Cicindelidae) - Duran, Daniel P. (Zootaxa, 2022)
The taxonomy of the tiger beetle genus Habroscelimorpha Dokhtouroff, 1883 is revised based on morphology, ecology, and molecular phylogenetics. Recently, nine Nearctic species of Habroscelimorpha were transferred to Eunota Rivalier, 1954 based on the same data types, but the Neotropical species have not been formally evaluated until the present publication. Herein I propose five new combinations based on a plurality of data, including morphological traits, ecology, and the topologies of three prior molecular studies, each based on three mitochondrial gene fragments (16S, COX3 and CytB): Eunota auraria (Klug, 1834) new combination, Eunota boops (Dejean, 1831) new combination, Eunota euryscopa (Bates, 1890) new combination, Eunota wellingi (Cassola and Sawada, 1990) new combination, Microthylax schwarzi (W. Horn, 1923) new combination.